2020
DOI: 10.1016/j.omto.2020.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Pseudostellaria heterophylla Extract Polysaccharide H-1-2 Suppresses Pancreatic Cancer by Inhibiting Hypoxia-Induced AG2

Abstract: We aimed to examine the therapeutic potential of polysaccharide H-1-2, a bioactive component of Pseudostellaria heterophylla, against pancreatic cancer, as well as to demonstrate the underlying molecular mechanisms. Invasion and migration of pancreatic cells treated with H-1-2 were evaluated. A xenograft tumor mouse model was established to assess the effect of H-1-2 on tumor growth. Expression levels of hypoxic inducible factor-1a (HIF1a) and anterior gradient 2 (AGR2) were measured in pancreatic cells after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The report showed that the purified polysaccharide has anti-inflammatory activity through activating the TLR4 signal pathways and decreasing the level of IL-1β and TNF-α ( You et al, 2021 ). Sun et al (2020) found that H-1–2 which is the purified polysaccharide in P. heterophylla has the inhibitory effect on pancreatic cancer. Meanwhile, polysaccharide in P. heterophylla has the effect of lowering blood sugar by stimulating insulin secretion level ( Chen et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The report showed that the purified polysaccharide has anti-inflammatory activity through activating the TLR4 signal pathways and decreasing the level of IL-1β and TNF-α ( You et al, 2021 ). Sun et al (2020) found that H-1–2 which is the purified polysaccharide in P. heterophylla has the inhibitory effect on pancreatic cancer. Meanwhile, polysaccharide in P. heterophylla has the effect of lowering blood sugar by stimulating insulin secretion level ( Chen et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…for diabetic nephropathy. H-1-2 is a novel polysaccharide of Pseudostellaria heterophylla, which has been reported to exert anti-hyperglycemic and anti-cancer effects in recent studies (Fang et al 2018, Sun et al 2020. Herein, we investigated whether H-1-2 ameliorates HG induced-podocyte depletion and EMT in vivo and ex vivo, and preliminarily uncovered the underlying mechanism.…”
Section: Accepted Manuscriptmentioning
confidence: 92%
“…MDA-MB-231 or MDA-MB-231-DTR cells were injected subcutaneously into the flanks of mice (4 × 10 6 cells in 200 µL PBS), and tumors were allowed to grow for 10 days until tumor volume reached approximately 100 mm 3 . The mice were randomized into vehicle control and treatment groups ( n = 6) [ 30 ]. Vehicle control (normal saline with 0.5% ( w / v ) Tween 80), docetaxel (10 mg/kg body weight), pulvomycin (10 mg/kg body weight), or a combination of docetaxel (10 mg/kg body weight) and pulvomycin (10 mg/kg body weight) was administered intraperitoneally (i.p.)…”
Section: Methodsmentioning
confidence: 99%